Achieving 100 %-efficiency joint in rotary friction welding of thin-walled Al alloy drive shafts via high friction pressure and short-time post-weld heat treatment - Kailiang Chen; Zexi Wu; Chunhui Ma; Licheng Sun; Wuran Lei; Ke He; Xiaoxue Chen; Yanquan Wu; Chunbo Zhang; Jun Zhou; Huihong Liu; Yongbing Li (Journal of Materials Research and Technology)
Rotary friction welding (RFW) was employed to join large diameter thin-walled Al–Mg–Si–Cu alloy drive shafts. The coupling effects of friction pressure and post-weld heat treatment (PWHT) on the microstructure evolution and mechanical properties of the RFWed joints were investigated. Increasing the friction pressure effectively enhanced the hardness of the softest area in heat affected zone (HAZ), due to the reduction in the peak welding temperature, which inhibited the annihilation of dislocation and the dissolution of precipitates and dispersions, thereby maintaining a high density of dislocations and an abundance of Q′ phases, β′ phases and α-Al(MnFe)Si dispersions in the softest area of the joints. Furthermore, higher friction pressure increased the cooling rate, resulting in no GP zones/pre-β'' phase precipitating during the cooling process, thereby retaining solute atoms within the Al matrix after RFW. Consequently, the combination of high friction pressure and short-time low-temperature PWHT at 180 °C for 60 min successfully improved the hardness of the softest area due to the precipitation of substantial spherical GP zones/pre-β'' phases using the solute atoms dissolved from Q′ and β′ phases at the abundant residual dislocations serving as nucleation sites. A high-performance RFWed joint of Al alloy exhibiting 100 % joint efficiency was therefore achieved for the first time in the large diameter thin-walled drive shafts.